Searching for a fabrication route of efficient Cu2ZnSnS4 solar cells by post-sulfuration of co-sputtered Sn-enriched precursors1. Issue 37 (7th October 2015) - Feng, Ye; Yu, Bing; Cheng, Guanming; Lau, Tszki; Li, Zhaohui; Yin, Ling; Song, Qiuming; Yang, Chunlei; Xiao, Xudong
<x xml:space="preserve">Abstract</x> The element contents and the annealing parameters, such as the peak annealing temperature, H2S concentration and the ramping rate, would strongly affect the remaining Sn contents in the Cu2ZnSnS4 thin films and greatly influence the device performance.